Tertiary treatment (Chlorella sp.) of a mixed effluent from two secondary treatments (immobilized recombinant P. pastori and rPOXA 1B concentrate) of coloured laboratory wastewater (CLWW) - Ardila-Leal, Leidy D. (3 Biotech, 2020)
Industrial development has increased wastewater (WW) volume; generating contamination and disturbing ecosystems, because of breeching disposal parameters. In this work, Coloured Laboratory Wastewater (CLWW), (1500.00 colour units, CU) was separately submitted to two secondary treatments. For the first one CLWW was treated for three cycles C1, C2 and C3 with P. pastoris X33/pGAPZαA-LaccPost-Stop producing rPOXA 1B laccase, immobilized in calcium alginate beads. For the second-one, rPOXA 1B enzyme concentrate was used (three processes: P1, P2, and P3). Both treatments were carried out in a 15 L reactor with 10 L effective work volume (EWV) with 72 h hydraulic retention time. C1, C2, and C3 effluents were flocculated and filtered through quartzite sand, while P1, P2, and P3 effluents were only filtered through quartzite sand. The mixture of secondary effluents was submitted to a tertiary treatment with Chlorella sp. For C1, C2, C3, P1, P2, and P3, CU removal was of 99.16, 99.58, 99.53, 96.72, 97.05 and 96.47%, respectively. Discharge parameters, total organic carbon (TOC), inorganic carbon (IC), chemical oxygen demand (COD) and biological oxygen demand (BOD(5)) decreased, although they reached different final values. After the tertiary treatment (144 h) effluent discharge parameters were reduced to 34 ± 4 CU, TOC to 6.6 ± 0.9 mg L(−1) and COD to 155 ± 4 mg L(−1). It was demonstrated that secondary treatments (immobilized recombined cells or recombinant enzyme concentrate) combined with Chlorella sp., (tertiary treatment) attained a considerable removal of discharge parameters, demonstrating a promissory alternative for CLWW sequential treatment.